2010
DOI: 10.1002/jbm.b.31740
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of ovine forestomach extracellular matrix biomaterials

Abstract: Ovine forestomach matrix (OFM) is a native and functional decellularized extracellular matrix biomaterial that supports cell adhesion and proliferation and is remodeled during the course of tissue regeneration. Small angle X-ray scattering demonstrated that OFM retains a native collagen architecture (d spacing = 63.5 ± 0.2 nm, orientation index = 20°). The biophysical properties of OFM were further defined using ball-burst, uniaxial and suture retention testing, as well as a quantification of aqueous permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…The single-ply lyophilized OFM, used in this study, has relatively low mechanical strength compared to the native tendon (load to failure of 15.07 N and suture pull-out of 5.91 N). However, OFM biomaterial has been fabricated into multi-ply presentations, with load to failures of over 65 N [ 37 ], allowing scope for a more mechanically robust augment through tailoring of the fabrication procedure. However, these were not practical to use in this study due to the relative size of the rat supraspinatus.…”
Section: Discussionmentioning
confidence: 99%
“…The single-ply lyophilized OFM, used in this study, has relatively low mechanical strength compared to the native tendon (load to failure of 15.07 N and suture pull-out of 5.91 N). However, OFM biomaterial has been fabricated into multi-ply presentations, with load to failures of over 65 N [ 37 ], allowing scope for a more mechanically robust augment through tailoring of the fabrication procedure. However, these were not practical to use in this study due to the relative size of the rat supraspinatus.…”
Section: Discussionmentioning
confidence: 99%
“…Type I collagen is also important in products made from animal skin, or related tissues, such as leather and extracellular matrix scaffolds for surgical applications. 1,2 Type II collagen has a fairly similar fibril structure to type I collagen, although with more branching and cross-linking, and is the main structural component of tissues, such as cartilage, therefore parallels may be drawn between type I and type II collagens. The mechanical properties of collagen-based materials are central to the natural and industrial uses of these materials and have been studied in a variety of tissues.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Structural components include elastin, fibronectin, and glycosaminoglycans. Structural studies have shown that CECM biomaterial is relatively strong and elastic and retains the complex collagen architecture of native tissue ECM.…”
Section: Discussionmentioning
confidence: 99%